Children's rights : multidisciplinary approaches to participation and protection - O'Neill, Tom, 1957-; Zinga, Dawn (University of Toronto Press, 2008)
Consisting of thirteen essays by prominent scholars, this volume is an in-depth and interdisciplinary exploration of the significance of children's rights, and a tremendous resource for those working with children and youth in institutional and educational settings.